Coordinated cyber‐physical attacks considering DoS attacks in power systems. (11th November 2019) - Tian, Jiwei; Wang, Buhong; Li, Tengyao; Shang, Fute; Cao, Kunrui
Summary: The smart grid faces a variety of physical and cyber attacks. Coordinated cyber‐physical attacks can cause severer consequences than the single cyber or physical attacks, which can be divided into two categories according to whether the physical attack is stealthy or not. Coordinated cyber‐physical attacks considering DoS attacks are investigated due to the lower cost of DoS attacks. In each category of coordinated cyber‐physical attacks, the mathematical models are derived and suitable methods are adopted to solve the corresponding issue. The experimental simulation demonstrates the potentially damaging effects and threats of this newly proposed attack. It is also presented that this newly proposed attack can use lower attack resources to introduce more catastrophic effects on the power system.